Optimizing the Capacity of Health Cadres in Child Growth and Development Screening Through the Web-Based Tool E-DDTK ASIK (Early Detection of Ideal Healthy Child Growth) - Arip, Moh; Ramadhan, Sahrir; Emilyani, Desty; Andini, Saskiyanti Ari (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Early detection of growth and development disorders will provide an opportunity for earlier stimulation. Early detection of growth and development deviations needs to be done to detect early deviations in toddler growth and development, including following up on any complaints from parents about their child's growth and development problems. The absence of target data that must be detected causes low coverage of the SDIDTK program, because parents do not know that their children must be detected for growth and development. The existing system still cannot provide fast, precise and accurate early information on cases of growth and development disorders, so training is needed on accessibility of child growth and development examinations through the development of a website-based SDIDTK model. It is hoped that health cadres in Suranadi Village, Suranadi Health Center area, will be able to conduct early detection of child growth and development using the E-DDTKASIK web-based application. The Community Service Team coordinated with partners in implementing this community service, namely the Suranadi Health Center. The target of the activity is 45 cadres in the Suranadi Health Center work area, the first stage is a pretest then socialization of the delivery of child growth and development materials and e-DDTK ASIK, after that a demonstration of the use of e-DDTK ASIK and a redemonstration for the participants and ending with a posttest to evaluate the knowledge of the cadres. All socialization and demonstration program activities were carried out well and smoothly, the location was appropriate and the participants actively participated in the activities.